Factors associated with mumps meningitis and the possible impact of vaccination - Kyuyol Rhie; Heung-Keun Park; Young-Soo Kim; Jung Sook Yeom; Ji Sook Park; Ji-Hyun Seo; Eun Sil Park; Jae-Young Lim; Chan-Hoo Park; Hyang-Ok Woo; Hee-Shang Youn (Korean Pediatric Society, 2016)
PurposeMumps meningitis is a common complication of mumps infection; however, information on mumps meningitis in the postvaccine era is limited. The purpose of the present study was to determine factors associated with mumps meningitis and to discuss the effect of vaccination on this disease.MethodsWe retrospectively reviewed patients younger than 19 years with mumps, diagnosed at a university hospital in Korea between 2003 and 2013. Patients were divided into groups with and without meningitis, and the clinical features of the 2 groups were compared.ResultsThe study enrolled 119 patients: 19 patients with meningitis and 100 patients without. Univariate analysis showed that older age (median: 15 years vs. 9.5 years, respectively), a longer interval from last vaccination (median: 10.2 years vs. 4.8 years, respectively), and febrile presentation (94.7% vs. 31.0%, respectively) were significantly associated with mumps meningitis. Sex, number of vaccination doses, bilateral parotitis, and the presence of complications other than meningitis did not differ between the 2 groups. In multivariate logistic regression analysis, age (odds ratio, 1.38; 95% confidence interval, 1.01-1.89; P=0.04) and fever (odds ratio, 30.46; 95% confidence interval, 3.27-283.61; P<0.01) remained independent factors for mumps meningitis.ConclusionClinicians in the postvaccine era should be aware of the possibility of mumps meningitis in febrile cases of mumps in adolescents, regardless of the number of vaccination doses. To establish the role of vaccination in mumps meningitis, further studies will be necessary.